Variasi dan Filogeni Kancil dan Napu (Tragulus Sp.) di Indonesia Menggunakan Gen 12s rRNA Mitokondria (VARIATION AND PHYLOGENI ON GENUS TRAGULUS (TRAGULUS SP.) IN INDONESIA USING MITOCHONDRIAL 12s rRNA GENE) - ., Wirdateti; Nugraha, Raden Taufiq Purna (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
Genus Tragulus in Indonesia is consisted of three species, namely Tragulus javanicus, T. napu, and T.kanchil. These three species are distributed in Kalimantan (Borneo), Java, Sumatra and Lesser Sundaislands. Taxonomically, based on morphological characteristic,T. javanicus is the same species as T. kanchil,while T. napu have differences in body size compared to the previous species. The status of genus Tragulusin Indonesia are protected by the law and categorized as least concern for T. napu and data deficient for T.javanicus in the IUCN Redlist. The aims of this study was to look at genetic variation among species andkinship based on mitochondrial DNA gene genus Tragulus. Genes used in this study was 12S ribosomalRNA with 300 bp long, using eight samples orginated from Singkep Islands (four individuals), MountHalimun, West Java (three individuals) and East Kalimantan (one individual). As a comparisons, publishednucleotide sequence of each species from GeneBank database were used. The results showed that thegenetic distances (d) between individuals is high d = 0.322 ± 0.023 with the nucleotide diversity (ð) =0.2402 which indicates that samples was consisted of samples from different species. Phylogenetic treebased on the nucleotide analysis indicatedthat these samples composed of three species namely T. javanicus,T. kanchil and T. napu. Samples from Mt. Halimun and East Kalimantan are clustered in one group,namely T. kanchil (Borneo) and T. javanicus (Mt. Halimun). Two samples from Singkep are clustered indifferent groups with the possibility as T. napu.
Keywords: Tragulus spp., 12S rRNA gene, molecular, diversity, genetic